Seeding variability of different alpha synuclein strains in synucleinopathies. Issue 5 (27th March 2019) - Candelise, Niccolò; Schmitz, Matthias; Llorens, Franc; Villar‐Piqué, Anna; Cramm, Maria; Thom, Tobias; da Silva Correia, Susana Margarida; da Cunha, José Eriton Gomes; Möbius, Wiebke; Outeiro, Tiago F.; Álvarez, Valentina González; Banchelli, Martina; et al.
Abstract : Objectives: Currently, the exact reasons why different α‐synucleinopathies exhibit variable pathologies and phenotypes are still unknown. A potential explanation may be the existence of distinctive α‐synuclein conformers or strains. Here, we intend to analyze the seeding activity of dementia with Lewy bodies (DLB) and Parkinson's disease (PD) brain‐derived α‐synuclein seeds by real‐time quaking‐induced conversion (RT‐QuIC) and to investigate the structure and morphology of the α‐synuclein aggregates generated by RT‐QuIC. Methods: A misfolded α‐synuclein–enriched brain fraction from frontal cortex and substantia nigra pars compacta tissue, isolated by several filtration and centrifugation steps, was subjected to α‐synuclein/RT‐QuIC analysis. Our study included neuropathologically well‐characterized cases with DLB, PD, and controls (Ctrl). Biochemical and morphological analyses of RT‐QuIC products were conducted by western blot, dot blot analysis, Raman spectroscopy, atomic force microscopy, and transmission electron microscopy. Results: Independently from the brain region, we observed different seeding kinetics of α‐synuclein in the RT‐QuIC in patients with DLB compared to PD and Ctrl. Biochemical characterization of the RT‐QuIC product indicated the generation of a proteinase K–resistant and fibrillary α‐synuclein species in DLB‐seeded reactions, whereas PD and control seeds failed in the conversion of wild‐type α‐synuclein substrate. Interpretation: Structural variances of α‐synuclein seeding kinetics and products in DLB and PD indicated, for the first time, the existence of different α‐synuclein strains in these groups. Therefore, our study contributes to a better understanding of the clinical heterogeneity among α‐synucleinopathies, offers an opportunity for a specific diagnosis, and opens new avenues for the future development of strain‐specific therapies. Ann Neurol 2019;85:691–703